Eksplorasi dan Perkembangbiakan Mikroba dari Makanan Fermentasi Khas Batak yang Berbasis Ikan Mas (Cyprinus Carpio) “Nanuira” serta Uji Sensitivitas terhadap Antibiotik - Sri Nanda; Ardi Mustakim (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Fermentation is one of the traditional food processing techniques that not only functions as a preservation method, but also plays a role in improving the nutritional quality and safety of food. One example of a typical Indonesian fermented food that has survived from generation to generation is naniura, a traditional dish of the Batak Toba people made from carp (Cyprinus carpio) which is processed without a cooking process. The fermentation process in naniura is carried out spontaneously by soaking in a solution of citrus (Citrus Sp.) and a mixture of local spices, thus creating an acidic environment that supports the growth of fermentative microorganisms, especially lactic acid bacteria (LAB). The purpose of this study was to isolate and identify LAB from naniura, as well as to carry out morphological characteristics, Gram staining, and sensitivity tests to several commonly used antibiotics. Isolation was carried out using MRS media in anaerobic conditions, while sensitivity tests were carried out using the disc diffusion method. The results showed that isolates from naniura had Gram-positive characteristics, rod-shaped, catalase negative, and showed varying inhibition zones against antibiotics. Some isolates showed resistance to amoxicillin and cefataxim, but were sensitive to erythromycin and gentamicin. These results indicate that LAB from naniura has potential as a probiotic candidate, but it is necessary to monitor the possibility of antibiotic resistance gene transfer.